2018
DOI: 10.1016/j.memsci.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of nanofiltration of weak electrolytes: SO42–/HSO4–/H+ system

Abstract: Over recent years, nanofiltration (NF) has been considered as an effective way to improve processing steps in metallurgical and hydrometallurgy applications dealing with mixtures of metal ions in sulphuric-acid-dominated solutions. The principal advantage of NF membranes over reverse osmosis (RO) membranes is their ability to allow for a practically free passage of acid, while metallic species, especially multi-charged species, are efficiently rejected. In general, these sulphuric solutions cover a range from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Related work that also considers pH effects and acid-base reactions is refs. [20][21][22][23][24], with some differences being that advection is neglected, membrane charge is not considered, and the model formulation uses virtual concentrations. Other related work focusing on extending the classical models, and including membrane charge and reactive ions, is refs.…”
Section: Introductionmentioning
confidence: 99%
“…Related work that also considers pH effects and acid-base reactions is refs. [20][21][22][23][24], with some differences being that advection is neglected, membrane charge is not considered, and the model formulation uses virtual concentrations. Other related work focusing on extending the classical models, and including membrane charge and reactive ions, is refs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the rejection of chloride by both NF membranes barely changes with pH, while the retention of sulfates decreases at pH 2, as a consequence of sulfate speciation into bisulfate and the higher positive zeta potential of the membranes. Several authors have also reported that speciation into bisulfate is responsible for the lower sulfate rejection as the pH is decreased [30,52]. Lopez et al argued that the transport of single-charged ions (such as HSO − 4 ) is favored over that of multi-charged ions by means of the dielectric exclusion phenomena [21].…”
Section: Electroplating Mixturementioning
confidence: 99%
“…A previous in-house study devoted to the effect of pH and membrane charge on the nanofiltration of acid mine drainage showed promising results in terms of simultaneous high heavy metals rejection and low rejection of sulfates, which can be utilized as a way of separating the metals from the accompanying sulfur-containing compounds [29]. The transport of inorganic species coupled to changes in their speciation has been studied by López et al [30], who also report a strong decrease in the rejection of total sulphate (SO 4 2− /HSO 4 − ) as the fraction of single-charged hydrogen sulphate (HSO 4 − ) in the feed increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, such as the weak electrolytes, ions can be presented as free ions and forming complexes between them, which have a noticeable impact on the separation performance. Some studies have coupled chemical equilibrium reactions with SD model [27,28].…”
Section: Introductionmentioning
confidence: 99%